The Effects of Representational Math in a Montessori Classroom - Horton, John (My University, 2016)
This Action Research Study is designed to evaluate the effect of integrating representational math in the Montessori classroom during mathematical instruction and practice. In comparative studies, Montessori students have generally out-performed non-Montessori peers in the area of mathematics during the initial years of schooling. However, around the 2nd grade, Montessori students seem to underperform in comparison to non-Montessori peers in certain mathematical competencies. This research took place in a public school classroom with 28 students, ranging in age from 6 to 9 years old. This quantitative study looked at data from a pretest and posttest given to students. By introducing representational pictures alongside Montessori math work during a 25-day intervention, students showed an increase in ability to solve addition and subtraction problems.
Keywords: number sense; concrete-representational-abstract; Montessori mathematics